Recurrent neural network classiﬁer for three layer conceptual network and performance evaluation - Md. Khalilur, Rhaman; Endo, Tsutomu (© 2010 ACADEMY PUBLISHER, 2016)
This article was published in JOURNAL OF COMPUTERS [© 2010 ACADEMY PUBLISHER] and the definite version is available at : http://www.jcomputers.us/vol5/jcp0501-05.pdf The article website is at: http://www.jcomputers.us/